2004
DOI: 10.1080/13576280410001711003
|View full text |Cite
|
Sign up to set email alerts
|

Educational Environment in Traditional and Innovative Medical Schools: A Study in Four Undergraduate Medical Schools

Abstract: The DREEM provides useful diagnostic information about medical schools, whether it is in developing or western developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
166
11
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(217 citation statements)
references
References 7 publications
26
166
11
14
Order By: Relevance
“…4 In a study performed by Al-Ayed & Sheik in Saudi Arabia, the lowest scores were related to the first domain (19.5) too. 16 This was reported (22.48) in studies by Al-Hazimi et al, with a score of 22.48, 17 a score of 25.8 in a study by Masood et al in Pakistan 18 and with a score of 25.5 in the present research. It can be concluded that in the traditional medical education system, the students' perception concerning learning was low.…”
Section: Discussionsupporting
confidence: 75%
“…4 In a study performed by Al-Ayed & Sheik in Saudi Arabia, the lowest scores were related to the first domain (19.5) too. 16 This was reported (22.48) in studies by Al-Hazimi et al, with a score of 22.48, 17 a score of 25.8 in a study by Masood et al in Pakistan 18 and with a score of 25.5 in the present research. It can be concluded that in the traditional medical education system, the students' perception concerning learning was low.…”
Section: Discussionsupporting
confidence: 75%
“…27 The results of this study showed the highest overall DREEM score that is reported in the published literature, which in turn means the existence of an excellent educational climate. 24,32 The only published results close to the result of the current study are from the United Kingdom: 69.5%, 36 70.4%, 37 and 71.5%. 38 To better delineate the strengths and weaknesses, the domains and analogous items of DREEM instrument were comparatively interpreted.…”
Section: General Considerationsmentioning
confidence: 70%
“…Interestingly, these items have been rated low in many other studies. 16,27,36,39,40 Hence, they can be generically weak areas of educational environment.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curriculum change was expected to build up a better learning environment, perceived as good by students [2]. A continuous improvement in this environment is only possible by defining its weaknesses and strengths [16].…”
Section: Discussionmentioning
confidence: 99%